Correction of idiopathic congenital talipes equinus varus by Ponseti technique in newborn - Bagul, Joti P.; Dole, Pankaj P. (International Journal of Research in Orthopaedics, 2019)
Background: Clubfoot is one of the commonest congenital anamoly. Though various modalities of treatment are available for this common disorder ranging from surgical release, distraction by external fixator to conservative methods none has proved to be standard for treatment. Methods: A study of 40 cases (62 feets) of clubfoot treatment was done at Post Graduate Institute of Swasthiyog Prathishthan, Miraj by Ponseti technique. Cavus was corrected in first manipulation by first metatarsal lift (supination) followed by forefoot adduction and heel varus in subsequent manipulation until abduction of 60-70 degree is achieved. Results: Post treatment evaluation of results was done. 75% feet had very good results, 20% had good results and 5% had poor results, 11% had relapse of deformity ranging from mild to severe. Two feets required retenotomy before casting, only one feet required RPMR. Conclusions: The Ponseti method of correction of clubfoot is a safe and effective treatment and radically decreases the need for extensive corrective surgeries and achieves functional pain free normal looking plantigrade feet with mobility and required no modified shoes.